Russian intelligence files on Asia. (Leiden, The Netherlands)
1 mikrofilm makarası (580 poz)
Keywords: Geographical, topographical, statistical, ethnographical and hydrographical intelligence : Geographical and topographical intelligence : European and Asian Turkey.